"Feita só por mãe!". Sentidos de maternidade e família entre mulheres prostitutas - Sganzella, Natália Cristina Marciola (2011)
This paper is an anthropological analysis of the love and family relationships of women involved in prostitution in Marília, besides other characters who are directly or indirectly linked to such practice. The objective of the research is to investigate these women s realm of relationships which include their family, love partner, and career. The methodological framework is ethnography through which contacts and exchanges have taken place with prostitutes in the city, and these elements are going to be presented in this dissertation. The paper shows two parts very distinctively marked both spatially and chronologically. The first part of the ethnography maps the relationships between the prostitution of women and the periods of the day. On the one hand, daytime on Nove de Julho Street mainly holds the prostitution of women in bars and hotels. They have more experience on the streets and in the occupation, and they form a more cohesive and less hierarchical group, which causes the relationships established at work to become family relationships. On the other hand, nighttime encompasses other types of prostitution, such as transvestites, making spatial and power relationships more limited and the area more competitive. There is a prestige hierarchy among the prostitution points according to the flow of the street, the prices charged, and the female attributes negotiated. The second part of the ethnography focuses on the family relationships that are developed in the points and homes of four of my interlocutors; motherhood and godmotherhood are strong factors in the structure of such families.